Quantitative explanation of circuit experiments and real traffic using the optimal velocity model - Akihiro Nakayama; Macoto Kikuchi; Akihiro Shibata; Yuki Sugiyama; Shin-ichi Tadaki; Satoshi Yukawa (New Journal of Physics, 2016)
We have experimentally confirmed that the occurrence of a traffic jam is a dynamical phase transition (Tadaki et al 2013 New J. Phys. http://dx.doi.org/10.1088/1367-2630/15/10/10303410.1088/1367-2630/15/10/103034 15 http://dx.doi.org/10.1088/1367-2630/15/10/10303410.1088/1367-2630/15/10/103034 , Sugiyama et al 2008 New J. Phys. http://dx.doi.org/10.1088/1367-2630/10/3/033001 10 http://dx.doi.org/10.1088/1367-2630/10/3/033001 ). In this study, we investigate whether the optimal velocity (OV) model can quantitatively explain the results of experiments. The occurrence and non-occurrence of jammed flow in our experiments agree with the predictions of the OV model. We also propose a scaling rule for the parameters of the model. Using this rule, we obtain critical density as a function of a single parameter. The obtained critical density is consistent with the observed values for highway traffic.